Challenges and Recommendations on the Development of Distributed Energy Resources (DERs) Datahub for Improved DERs Data Management in Malaysia - Ramasamy A.; Aris H.; Abdul Latif A.; Malek S.N.H.; Abdul Latif S.; Kaur K.D. (Springer Science and Business Media Deutschland GmbH, 2023)
Advanced metering infrastructures; Data integration; Electric power generation; Electric power transmission networks; Electric utilities; Energy management; Fossil fuels; Information management; Renewable energy resources; Smart meters; % reductions; Distributed Energy Resources; Distribution grid; Electricity-generation; Energy demands; Energy informatics; Malaysia; Policies and measures; Renewable energies; Technical challenges; Energy efficiency